BEHAVIOR OF THEORETICAL CURVE NUMBERS WITH RESPECT TO SOIL AND RAINFALL PROPERTIES - T. Y. Gan (International Association of Lowland Technology, 2002)
A dimensional analysis fails to obtain a universal, dimensionless relationshop between the maximum retention potential (S) of the Soil Conservation Service (SCS), runoff curve numbers (CN), and saturated hydraulic conductivity Ks, sorptivity, rainfall parameters, surface runoff, and soil moisture. Next, both S and the theoretical CN (CNT) were calibrated based on the numerical solutions of Richard’s equation applied to homogeneous soil columns. Result show that S and CNT are directly related to soil but inversely related to rainfall properties. As a temporally-lumped model, CN generally estimated lower cumulative infiltration than that of Richard’s equation; and in practice, the CN method may perform poorly if (1) Antecedent Moisture Conditions (AMC) is low, (2) the initial rainfall is much higher than Ks which leads to Horton overland florw, or (3) the rain pulses after the initial abstraction is satisfied are small. Before applications, adjustment of CNT with respect to the standart CN of fallow/idle land to reflect the effect of landuse, land treatment, and hydrologic conditions are recomended.